Numerical Analysis of Flow and Heat Transfer Characteristics of CO2 at Vapour and Supercritical Phases in Micro-Channels - N. T., Rao; A. N., Oumer; Ummu Kulthum, Jamaludin; A. Y., Adam (EDP Sciences, 2016)
Supercritical carbon dioxide (CO2) has special thermal properties with better heat transfer and flow characteristics. Due to this reason, supercritical CO2 is being used recently in air-condition and refrigeration systems to replace non environmental friendly refrigerants. Even though many researches have been done, there are not many literatures for heat transfer and flow characteristics of supercritical CO2. Therefore, the main purpose of this study is to develop flow and heat transfer CFD models on two different phases; vapour and supercritical of CO2 to investigate the heat transfer characteristics and pressure drop in microchannels. CO2 is considered to be in different phases with different flow pressures but at same temperature. For the simulation, the CO2 flow was assumed to be turbulent, non-isothermal and Newtonian. The numerical results for both phases are compared. From the numerical analysis, for both vapour and supercritical phases, the heat energy from CO2 gas transferred to water to attain thermal equilibrium. The temperature of CO2 at vapour phase decreased 1.78% compared to supercritical phase, which decreased for 0.56% from the inlet temperature. There was a drastic increase of 72% for average Nu when the phase changed from vapour to supercritical. The average Nu decreased rapidly about 41% after total pressure of 9.0MPa. Pressure drop (P) increased together with Reynolds number (Re) for vapour and supercritical phases. When the phase changed from vapour to supercritical,P was increased about 26%. The results obtained from this study can provide information for further investigations on supercritical CO2.